Synchronization : - Pikovsky, Arkady (Cambridge University Press, 2001)
The first half of this book describes synchronization without formulae, and is based on qualitative intuitive ideas. The second half of the book presents the main effects of synchronization in a rigorous and systematic manner, describing both classical results on synchronization of periodic oscillators and recent developments in chaotic systems, large ensembles, and oscillatory media.